ダイ 34 ジ ナンキョク チイキ カンソクタイ エットウ ホウコク 1993-1994 - 佐藤, 夏雄; サトウ, ナツオ; Sato, Natsuo (1999)
P(論文) 第34次南極地域観測隊越冬隊は, 越冬隊長佐藤夏雄以下40名で構成され, 1993年2月1日から1994年1月31日までのあいだ, 昭和基地の運営・維持管理を行うとともに, 計画に基づき昭和基地, 沿岸, 内陸で観測および設営活動を行った。越冬期間の主な研究観測計画は, 2年越しの超伝導重力計の設置観測, ドームF(現在ドームふじ観測拠点)までの内陸旅行等であった。超伝導重力計に関しては, 3月に装置が立ち上がり連続長期観測データが得られた。内陸旅行も, 冬開けには中継拠点までの旅行と夏のドームFまでの本旅行も予定どおりに実施できた。その他の宙空系, 地学系, 気水圏系, 生物系の観測も順調に実施できた。定常観測も順調に経過し, 気象部門の観測では, オゾンホールの発達を今回も捕らえる事ができた。設営関係も順調に経過し, 基地の維持・運営及び観測関係のサポートに大きく貢献した。生活面では, 管理棟内の食堂, バーや医務室などの内部設備が完成し, 使用を開始したため, この棟が生活の中心の場となった。なお, 年間の気候は気温が低く, かつブリザードに度々襲来され, かなり厳しい気象条件下での越冬であった。 The wintering party of the 34th Japanese Antarctic Research Expedition (JARE-34), which consisted of 40 members including one foreign scientist, wintered at Syowa Station from February 1993 to January 1994. Observations at Syowa Station were conducted on various subjects such as meteorology, upper atmosphere physics, ionosphere, solid earth science and environmental science. A superconducting gravimeter was newly installed and the Earth's free oscillations were observed. The total ozone content reached a minimum value in October 1993. Intensive field activities in geology, geomagnetism, marine biology and glaciology were carried out in the coastal areas and inland plateau. The wintering period of JARE-34 was the 2nd year of the deep ice core drilling project at Dome Fuji Station. Several inland traverse parties were sent to the relay-point and Dome Fuji Station to transport fuel and construction materials. Nine members stayed at Dome Fuji Station for more than three months in the austral summer of 1993 to 1994 and constructed some buildings for ice drilling. The Syowa Station facilities were maintained very well through the efforts of the logistic members. departmental bulletin paper